En hardback-revolution? - Pristed, Birgitte Beck (Passage - Tidsskrift for litteratur og kritik, 2010)
Birgitte Beck Pristed: "En hardback-revolution? - Om sovjetisk bogdesign 1935-1960" Abstract Birgitte Pristed: “A Hardback Revolution?: Soviet Book Design 1935-1960” In Western book history the period 1935-60 has often been referred to as a “paperback revolution”. However, in the USSR the relation between fiction titles in hard covers and paper covers developed opposite to the Western trend, towards a consolidation of the hardback in the post-war period. The rise of the cheap, but solid, standardised, mass produced Soviet hardback was closely connected to the shifts in Soviet publishing politics and emphasized the role and status of literature in Soviet book culture.